Valorization of lignocellulosic biomass for polyhydroxyalkanoate production: Status and perspectives. (September 2022) - Sohn, Yu Jung; Son, Jina; Lim, Hye Jin; Lim, Seo Hyun; Park, Si Jae
Graphical abstract: Highlights: LCB-to-PHA production model outlines the zero plastic waste and circular bioeconomy. LCB holds a great potential for both of natural and non-natural PHA production. Metabolically engineered host strains accelerate the mass production of PHA from LCB. Further expansion of PHA portfolios using LCB as the main resource can be envisioned. Abstract: With the increasing concerns regarding climate, energy, and plastic crises, bio-based production of biodegradable polymers has become a dire necessity. Significant progress has been made in biotechnology for the production of biodegradable polymers from renewable resources to achieve the goal of zero plastic waste and a net-zero carbon bioeconomy. In this review, an overview of polyhydroxyalkanoate (PHA) production from lignocellulosic biomass (LCB) was presented. Having established LCB-based biorefinery with proper pretreatment techniques, various PHAs could be produced from LCB-derived sugars, hydrolysates, and/or aromatic mixtures employing microorganisms. This provides a clue for addressing the current environmental crises because "biodegradable polymers" could be produced from one of the most abundant resources that are renewable and sustainable in a "carbon-neutral process". Furthermore, the potential future of LCB-to-non-natural PHA production was discussed with particular reference to non-natural PHA biosynthesis methods and LCB-derived aromatic mixture biofunnelling systems.